2018
DOI: 10.3892/ol.2018.9128
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic and prognostic value of plasma microRNA‑125b‑5p in patients with multiple myeloma

Abstract: Abstract. Aberrant expression of microRNAs (miRNAs) contributes to the progression and outcomes of several types of tumor, while circulating miRNAs have been reported to act as biomarkers for several types of cancer. To identify specific circulating miRNAs associated with multiple myeloma (MM), a miRNA microarray analysis was used, which identified 8 upregulated miRNAs and 4 downregulated miRNAs in the plasma of 6 patients with MM compared with 6 healthy individuals. Based on the microarray results, the 8 miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 36 publications
(33 reference statements)
2
30
0
Order By: Relevance
“…In EOC, Zuberi and colleagues [17] demonstrated that serum levels of miR-125b were higher in most patients with cancer and were associated with cancer development, which could be a potential diagnostic and prognostic marker in clinical practice. More importantly, miR-125b may also have potential as a cancerspecific serum biomarker for various human cancers [19][20][21]. Other previous studies showed the enforced miR-125b had a potent antitumor activity in vitro and in vivo models of therapy against EOC [15,22,23].…”
Section: Discussionmentioning
confidence: 91%
“…In EOC, Zuberi and colleagues [17] demonstrated that serum levels of miR-125b were higher in most patients with cancer and were associated with cancer development, which could be a potential diagnostic and prognostic marker in clinical practice. More importantly, miR-125b may also have potential as a cancerspecific serum biomarker for various human cancers [19][20][21]. Other previous studies showed the enforced miR-125b had a potent antitumor activity in vitro and in vivo models of therapy against EOC [15,22,23].…”
Section: Discussionmentioning
confidence: 91%
“…Together, these previous studies suggested that identification of cancer-associated biomarkers for tumor progression and outcome may help to predict patient prognosis and treatment strategies. A number of miRNAs have been demonstrated to contribute to the development of cancer and to serve as biomarkers for the diagnosis, prognosis or treatment of different types of cancer (30)(31)(32). Taheriazam et al (33) demonstrated that miRNA-130b expression was increased in OS tissues, whereas, the level of miRNA-218 expression was downregulated; these miRNAs may serve as potential biomarkers in the early detection of OS.…”
Section: Discussionmentioning
confidence: 99%
“…Serum analysis revealed a combination of up-regulated miR-34a and down-regulated let-7e could distinguish MM from control with a sensitivity and specificity of 80%, and MGUS with a sensitivity and specificity of over 90% ( Table 3 ) [ 183 ]. Other suggested markers include increased plasma miR-125b-5p, serum miR-29a, serum miR-4449, and decreased serum miR-30d and miR-203 levels [ 184 , 185 , 186 , 187 , 188 ]. In addition, the miR-125b-5p level was associated with extramedullary infiltration and was significantly higher in stage III patients compared to stage I/II patients [ 184 ].…”
Section: Circulating Mirnas As Biomarkers For MM Diagnosismentioning
confidence: 99%
“…Other suggested markers include increased plasma miR-125b-5p, serum miR-29a, serum miR-4449, and decreased serum miR-30d and miR-203 levels [ 184 , 185 , 186 , 187 , 188 ]. In addition, the miR-125b-5p level was associated with extramedullary infiltration and was significantly higher in stage III patients compared to stage I/II patients [ 184 ]. Similarly, plasma miR-483-5p level in MM patients was also found to be correlated with ISS stage [ 189 ].…”
Section: Circulating Mirnas As Biomarkers For MM Diagnosismentioning
confidence: 99%